Screening in the era of HPV vaccine - Jerónimo, José (2015)
There is much expectation on the introduction of prophylactic vaccines against human papilloma virus specifically against 16 and 18 oncogenic type, as theoretically would permit to prevent approximatelly 70% of uterine cervical cancer in the world. The vaccine has been approved in some countries and there is the intention to introduce it in the national programs of immunizations. For example, some states of the United States of North America are considering vaccination obligatory in girls in school age. The objective of this chapter is to determine the effect vaccination would have in uterine cervical cancer screening. For such we need to review the natural history of HPV infection by cervical neoplasia.